A Cholesky-based estimation for large-dimensional covariance matrices. Issue 6 (25th April 2020) - Kang, Xiaoning; Xie, Chaoping; Wang, Mingqiu
ABSTRACT: This paper develops a new method to estimate a large-dimensional covariance matrix when the variables have no natural ordering among themselves. The modified Cholesky decomposition technique is used to provide a set of estimates of the covariance matrix under multiple orderings of variables. The proposed estimator is in the form of a linear combination of these available estimates and the identity matrix. It is positive definite and applicable in large dimensions. The merits of the proposed estimator are demonstrated through the numerical study and a real data example by comparison with several existing methods.